CLIPON: A CRISPR‐Enabled Strategy that Turns Commercial Pregnancy Test Strips into General Point‐of‐Need Test Devices. (2nd February 2022) - Tang, Yidan; Qi, Lijuan; Liu, Yichen; Guo, Lulu; Zhao, Rujian; Yang, Meiting; Du, Yan; Li, Bingling
Abstract: Desirable biosensing assays need to be sensitive, specific, cost‐effective, instrument‐free, and versatile. Herein we report a new strategy termed CLIPON (C RISPR and L arge DNA assembly I nduced P regnancy strips for signal‐ON detection) that can deliver these traits. CLIPON integrates a commercial pregnancy test strip (PTS) with four biological elements: the human chorionic gonadotropin (hCG), CRISPR‐Cas12a, crRNA and c auliflower‐like l arge‐sized D NA assemblies (CLD). CLIPON uses the Cas12a/crRNA complex both to recognize a target of interest and to release CLD‐bound hCG so that target presence can translate into a colorimetric signal on the PTS. We demonstrate the versatility of CLIPON through sensitive and specific detection of HPV genomic DNA, SARS‐CoV‐2 genomic RNA and adenosine. We also engineer a cell phone app and a hand‐held microchip to achieve signal quantification. CLIPON represents an attractive option for biosensing and point‐of‐care diagnostics. Abstract : By rational integration of the human chorionic gonadotropin, CRISPR‐Cas12a/crRNA system, and large‐sized DNA assemblies, a portable sensing platform termed CLIPON has been developed, which can transduce both nucleic acid and non‐nucleic acid targets into commercial pregnancy test strip readout. The detection is sensitive, selective, instrument‐free, and allows future integration into a microchip.